Faktor-Faktor yang Memengaruhi Keberhasilan Pelaksanaan Redistribusi Tanah Bekas Kawasan Hutan - Festi Kurniawati; Sri Kistiyah; Ahmad Nashih Luthfi (Sekolah Tinggi Pertanahan Nasional, 2019)
Abstract: Land redistribution in South Kalimantan Province in 2018 was carried out in 11 districts with a commitment level of 51.42%. Hulu Sungai Selatan Regency is the only district in South Kalimantan Province that has achieved 100% realization of activities. The land came from former forest areas. This research was conducted to identify and explain the factors influenced the successful of land redistribution implementation in Hulu Sungai Selatan Regency. To answer these questions, the researcher developed the framework from theoretical key models for the success of land redistribution by Joyo Winoto and Russell King. The analysis was conducted with qualitative descriptive approach. Research data obtained from the interview and study of related documents. Research data were obtained from interviews and related study studies. The results showed that, the successful implementation of land redistribution is influenced by factors: the political will to form the landreform consideration committee; the ruling elite has no political interest in Landform Land Object; and the involvement of the regional government, HKTI, and banks in access reform activities.Keywords: agrarian reform, redistribution of landreform object from former forest areas, successful land redistribution implementation.Intisari: Redistribusi tanah di Provinsi Kalimantan Selatan pada tahun 2018 dilaksanaan di 11 kabupaten dengan tingkat realisasi sebesar 51,42%. Kabupaten Hulu Sungai Selatan merupakan satu-satunya kabupaten di Provinsi Kalimantan Selatan yang berhasil mencapai realisasi kegiatan sebesar 100%. Tanah tersebut berasal dari tanah bekas Kawasan Hutan. Penelitian ini dilakukan untuk mengidentifikasi dan menjelaskan faktor-faktor yang memengaruhi keberhasilan pelaksanaan redistribusi tanah di Kabupaten Hulu Sungai Selatan. Untuk menjawab pertanyaan tersebut, penulis mengembangkan model teori kunci keberhasilan redistribusi tanah dari Joyo Winoto dan Russel King. Analisis penelitian dilakukan dengan pendekatan deskriptif kualitatif. Data penelitian diperoleh dari wawancara dan studi dokumen terkait. Hasil penelitian menunjukkan bahwa keberhasilan pelaksanaan redistribusi tanah dipengaruhi oleh faktor-faktor diantaranya adalah adanya political will untuk membentuk Panitia Pertimbangan Landreform; elite penguasa tidak memiliki politic interest terhadap Tanah Obyek Landreform; dan keterlibatan pemerintah daerah, HKTI, dan pihak perbankan dalam kegiatan access reform.Kata kunci: reforma agraria, redistribusi tanah bekas kawasan hutan, keberhasilan redistribusi tanah.